IMPLEMENTASI PERATURAN DAERAH KOTA DUMAI NOMOR 5 TAHUN 2020 TENTANG PERUBAHAN ATAS PERATURAN DAERAH KOTA DUMAI NOMOR 4 TAHUN 2012 TENTANG PAJAK SARANG BURUNG WALET - Khansen Pranata Wirantober; Emilda Firdaus; Zainul Akmal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Regional Original Revenue or commonly called PAD is one type of regional incomeor revenue which is greatly influenced by how a region maximizes its potential andresources. The greater the contribution of PAD revenue to the APBD, the higher the level ofindependence of the region and the smaller the level of regional dependence on the centerand also shows the better a region is in managing the potential and resources they have. Oneof the revenues in PAD is Regional Taxes. The central government gives great authority tothe Province to manage and collect seven types of taxes. Then for the Regency / City is giventhe authority to manage and collect nine types of taxes. One type of revenue in PAD in theRegency / City is the Swallow's Nest Tax. Swallow's Nest Tax is a tax on the collection and/orexploitation of Swallow's Nest.Given the relatively high price of swallow's nest, many people in Indonesia conductswallow cultivation by building houses or multi-storey buildings to serve as swallow habitatsto live and breed. One of the regencies/cities where many people cultivate swiftlets is DumaiCity, located in Riau Province. So that the Dumai City Government issued Dumai CityRegional Regulation Number 5 of 2020 concerning Amendments to Dumai City RegionalRegulation Number 4 of 2012 concerning Swallow Nest Tax as a judicial basis for itsimplementation. This is considered important so that the revenue of Swallow Nest Tax inDumai City can be carried out properly and maximally.Based on the results of temporary observations, the implementation of the regulationhas not gone as expected. This is based on the fact that many swallow entrepreneurs are notwell informed about this local regulation. This is further supported by data from BAPENDADumai City, namely that of the nine types of local taxes that are a source of income forDumai City, there are three taxes whose realization percentage has not reached one hundredpercent in 2021, one of which is the Swallow Nest Tax which has the lowest percentage,namely 79.12%. Then from the target and realization data specifically on swallow's nest taxin Dumai City. In 2020 and 2021 the amount of swallow's nest tax realization is still far fromthe target.Based on the description of the problems described above, the authors would like tofurther examine the implementation of the Regional Regulation on Swallow Nest Tax. Inorder to see how the implementation of the regulation, including the factors that influence theobstruction of the implementation of the regulation and what efforts can be made toanticipate the inhibiting factors of the regulation.Keywords: Swallow's nest tax, local regulations, taxpayers, Bapenda, implementation.